Long-term effect of pH on denitrification: High pH benefits achieving partial-denitrification - Qian, Wenting; Ma, Bin; Li, Xiyao; Zhang, Qiong; Peng, Yongzhen (Bioresource technology, 2019)
[Display omitted] •Partial-denitrification is a feasible way to supply nitrite for anammox.•Nitrite accumulation rate (NAR) increased with pH during denitrification.•The higher NAR at pH 9.0 was correlated with an enrichment of Thauera.•Thauera harbored more nitrate reductase than nitrite reductase.•A process for achieving partial denitrification/anammox in WWTP was proposed. Partial-denitrification (nitrate to nitrite) can supply nitrite for anammox which can reduce organic matter consumption in wastewater treatment plants (WWTPs). In order to achieve stable partial-denitrification, the effect of pH on denitrification were investigated for 420 days in three reactors with influent pH of 5.0, 7.0 and 9.0. The results indicate that the nitrite accumulation rate (NAR) increased with pH, with average effluent NARs being 21%, 38% and 57% in the above reactors, respectively. The sludge cultivated at a high pH of 9.0 was resistant to pH shock, with a high NAR being maintained at 83% when it was exposed to a low pH of 5.0. Metagenomic analysis showed that the higher NAR at pH 9.0 was correlated with an enrichment of Thauera, which harbored more nitrate reductase (8098 hits) than nitrite reductase (2950 hits). Based on these findings, a novel process was proposed for achieving partial-denitrification/anammox in mainstream WWTPs.